Design and fabrication of {111}-textured nanotwinned silver coating for enhancing surface wear resistance of depleted uranium - Kunming Yang; Xiaobo Wang; Shengfa Zhu; Yawen Zhao; Qingdong Xu; Yiyun Wei; Chao Lu; Zhiyuan Wen; Tongxiang Fan; Mingyu Gong; Anyi Yin; Wenhua Luo (Journal of Materials Research and Technology)
Enhancing surface wear resistance is critical for uranium (U) and its alloys to retard degradation of their mechanical and physical properties. Deposited nanotwinned (NT) silver (Ag), which is relatively “soft” in-plane and “hard” out-of-plane with respect to surface, may serve as wear-resistant coating. In this work, first-principles density functional theory (DFT) calculations were performed to reveal the energetics of possible Ag/α-U interfaces. Meanwhile, molecular statics (MS) and molecular dynamics (MD) simulations were carried out to understand the behaviors of Ag adatoms and the tribological performance of subsequent different textured Ag. The {111}Ag-textured coating with fine twins with small plastic zone, low delamination height and subsequent minimal coefficient of friction (COF) was designed. Furthermore, by controlling the bias voltage of magnetron sputtering from −100 to −800 V, Ag coatings with various surface roughness, grain size, and nanoscale twin density were experimentally deposited on depleted uranium (DU) for tribological performance studies. Microstructural characterizations showed that at the optimized bias voltage of −400 V, the sputter-deposited Ag coating exhibited {111}-oriented texture with high-density nanoscale twins and also well-bonded Ag/DU interface with an UO2 interlayer, thus endowing the Ag coating highly stable wear resistance with low mass wear rate of ∼1.37 × 10−7 g/(N·s). The present findings may shed lights on microstructural and interface design of surface anti-wear coatings on U and its alloys.